"Library 4 You Program": shaping and revitalizing relationships between patron and library - Mohamad Kasim, Suzila; Sayuti, Rusniah; Abd Hadi, Azana; Md Nazar, Aznizultina; Samsuddin, Samsul Farid (Department of Library and Information Science, Faculty of Computer Science and Information Technology, University of Malaya and University of Malaya Library, 2019)
Although the academic library has it owns specific patrons compared to public libraries, the challenges in encouraging users to visit the library still one of the issues especially the millennial generations nowadays. In conjunction with the issue, an initiative has been taken by UPM Library to conduct the “Library 4 You Program” for the purpose of bringing the library nearer to the users. The aim of this paper is to share the initiatives taken by an academic library in shaping good relationship between library and its patrons as a best practice. The data for this study were collected through documents, personal experiences and observations from the program implementation. The study also focused on the arrangements and activities done throughout the program. Pictures were included in this paper to show the actual activities and programs conducted. This initiative has been conducted yearly as one of the library programs in collaboration between library and faculty members. UPM Library had found that this program is a positive approach in promoting the library services and facilities to the patrons by bringing the library to them. The library promotions, strategic alliances and partnership among faculty members can help to revitalize the library and stay relevant. The Library 4 You Program could also close the gaps between librarian and user which exists in certain libraries across the region. Along with the experience sharing, the limitation of this paper it was done within the academic library setting. It may differ in approach according to the types of that specific library.